2022
DOI: 10.1111/andr.13209
|View full text |Cite
|
Sign up to set email alerts
|

Covid‐19 vaccination BNT162b2 temporarily impairs semen concentration and total motile count among semen donors

Abstract: Background: The development of covid-19 vaccinations represents a notable scientific achievement. Nevertheless, concerns have been raised regarding their possible detrimental impact on male fertility Objective: To investigate the effect of covid-19 BNT162b2 (Pfizer) vaccine on semen parameters among semen donors (SD). Methods: Thirty-seven SD from three sperm banks that provided 216 samples were included in that retrospective longitudinal multicenter cohort study. BNT162b2 vaccination included two doses, and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 39 publications
1
42
0
2
Order By: Relevance
“…A study by Gat et al on semen of male semen donors revealed a transient decrease in semen concentration and a reduction in the total motile count (TMC) after COVID-19 vaccination [64].…”
Section: Short Term Side Effectsmentioning
confidence: 99%
“…A study by Gat et al on semen of male semen donors revealed a transient decrease in semen concentration and a reduction in the total motile count (TMC) after COVID-19 vaccination [64].…”
Section: Short Term Side Effectsmentioning
confidence: 99%
“…Over 145 days after the end of vaccination, the values of these same parameters had also decreased by 15.9% and 19.4%, respectively, compared to prevaccination levels, but without reaching statistical significance. [ 71 ]…”
Section: Covid-19mentioning
confidence: 99%
“…Over 145 days after the end of vaccination, the values of these same parameters had also decreased by 15.9% and 19.4%, respectively, compared to prevaccination levels, but without reaching statistical significance. [71] As regards long-term side effects, a parallel could be drawn with vaccines in general. e two main categories of diseases reported in the biomedical literature triggered by vaccinations are autoimmune: systemic lupus erythematosus, multiple sclerosis, hepatitis, Guillain-Barre syndrome (GBS), etc.…”
Section: Unknown Risksmentioning
confidence: 99%
“…We would like to share our views on the article “Covid‐19 vaccination BNT162b2 temporarily impairs semen concentration and total motile count among semen donors.” 1 According to Gat et al., a systemic immune response following BNT162b2 immunization is responsible for temporary semen concentration and total motile count (TMC) reduction, and long‐term prognosis remains favorable. 1 Although the COVID‐19 vaccine is effective, it may have detrimental effects as well. Some of the adverse effects of immunization reported in the current study, such as altering the semen concentration and TMC of participants, could have negative consequences.…”
mentioning
confidence: 99%